Learning Environment in Physical Education in Šakiai and Šakiai District: Comparative Analysis - Laima Trinkūnienė; Edvinas Vensas (Lithuanian Sports University, 2018)
Background. According to various research publications, physical education teachers work in the environment where  the  teaching process  is  often  hindered by  low  physical  education subject status,  insufficient number  and quality of lessons, lack of facilities and equipment for learning and the environment which is neither functional nor safe or hygienic. Concerned about pupils' physical activity decrease in secondary schools, Education and Sports Department of Šakiai District Municipality submitted a request to Physical Education study programme director of Lithuanian Sports University to carry out research revealing the existing situation about physical education and sports infrastructure in Šakiai district secondary schools. The aim of our study was to compare physical education environment in Šakiai and Šakiai district high schools, junior gymnasiums and lower secondary schools. Methods.  We  used  a  questionnaire  for  the  survey  drafted  in  the  international  study  by  Sport  Science  and Physical Education Council (ICSSPE / IOC) (Hardman & Marshall, 2009) and other references. During the study, we interviewed 13 physical education teachers from 14 Šakiai city and Šakiai district schools (2 women and 11 men). Results. The quality of learning tools in city schools was seen as excellent or good, while the quantity was also seen only as extensive or above average. Obtained results in the district schools varied, but most of them indicated that the quality (33%) and quantity (50%) was only adequate or sufficient. Physical education subject status in comparison with other subjects in half of the city schools was seen as the same and in the other half - as lower. In most schools in the district, it was seen as the same (92%). City schools did not lack hygienic equipment, but a significant number of district schools did not have changing rooms with lockers and hangers (33%) and showers (25%). In the district schools that had showers, they were not used in 56% of them. Conclusions. Schools in the city are supplied with more and better teaching tools and equipment. Physical Education subject status in half of city schools is perceived as inferior to other subjects. Hygiene conditions in city schools are good compared to the district schools, where they are poor. Keywords:  physical education, learning equipment, learning environment, status, hygiene conditions.